2022
DOI: 10.1108/ijot-08-2021-0019
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation in dementia: CST and Sonas group interventions for people with moderate cognitive impairment. A pilot study

Abstract: Purpose Dementia is a complex, progressively degenerative condition. It results in loss of cognitive and functional capabilities, along with a significant increase in the level of dependency. A reduction in the use of pharmacological interventions correlates with an increased in good quality non-pharmacological interventions in dementia care. The purpose of this study is to examine the impact of 14-session face-to-face cognitive stimulation therapy (CST) and Sonas group interventions on individuals living with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Neither Spector et al (2003) or Coen et al (2011) found significant between-group differences in functional ability when compared to a usual-care control group. No significant between-group differences in ADL performance were also reported in Dolan et al’s (2022) study comparing CST to Sonas.…”
Section: Resultsmentioning
confidence: 59%
See 4 more Smart Citations
“…Neither Spector et al (2003) or Coen et al (2011) found significant between-group differences in functional ability when compared to a usual-care control group. No significant between-group differences in ADL performance were also reported in Dolan et al’s (2022) study comparing CST to Sonas.…”
Section: Resultsmentioning
confidence: 59%
“…Eight papers included in this review evaluated an intervention of CST. Spector et al’s (2003) RCT originally trialled the English format of CST ( N = 201), which two smaller-scale, Irish-based trials further evaluated (Coen et al, 2011; Dolan et al, 2022). All three studies involved 45-minute group sessions run twice weekly for a duration of 7 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations